The future of the site (Scottish Archaeological Internet Reports, 2004)
The excavations demonstrated that stratified Mesolithic deposits survive at Camas Daraich. Much of the site lies relatively undisturbed under the ploughsoil across the croft, and there is a high possibility that later deposits also occur. A small amount of archaeological material is threated by natural erosion along the course of the new track and all is vulnerable to any further development in the croft area. It is to be hoped that Historic Scotland can implement measures to minimize further destruction and monitor any disturbance that might take place.